Oxadiazon affects the expression and activity of aldehyde dehydrogenase and acylphosphatase in human striatal precursor cells: A possible role in neurotoxicity. (1st January 2019) - Degl'Innocenti, Donatella; Ramazzotti, Matteo; Sarchielli, Erica; Monti, Daniela; Chevanne, Marta; Vannelli, Gabriella Barbara; Barletta, Emanuela
Abstract: Exposure to herbicides can induce long-term chronic adverse effects such as respiratory diseases, malignancies and neurodegenerative diseases. Oxadiazon, a pre-emergence or early post-emergence herbicide, despite its low acute toxicity, may induce liver cancer and may exert adverse effects on reproductive and on endocrine functions. Unlike other herbicides, there are no indications on neurotoxicity associated with long-term exposure to oxadiazon. Therefore, we have analyzed in primary neuronal precursor cells isolated from human striatal primordium the effects of non-cytotoxic doses of oxadiazon on neuronal cell differentiation and migration, and on the expression and activity of the mitochondrial aldehyde dehydrogenase 2 (ALDH2) and of the acylphosphatase (ACYP). ALDH2 activity protects neurons against neurotoxicity induced by toxic aldehydes during oxidative stress and plays a role in neurodegenerative conditions such as Alzheimer's disease and Parkinson's disease. ACYP is involved in ion transport, cell differentiation, programmed cell death and cancer, and increased levels of ACYP have been revealed in fibroblasts from patients affected by Alzheimer's disease. In this study we demonstrated that non-cytotoxic doses of oxadiazon were able to inhibit neuronal striatal cell migration and FGF2- and BDNF-dependent differentiation towards neuronal phenotype, and to inhibit the expression and activity of ALDH2 and to increase the expression and activity of ACYP2. In addition, we have provided evidence that in human primary neuronal precursor striatal cells the inhibitory effects of oxadiazon on cell migration and differentiation towards neuronal phenotype were achieved through modulation of ACYP2. Taken together, our findings reveal for the first time that oxadiazon could exert neurotoxic effects by impairing differentiative capabilities of primary neuronal cells and indicate that ALDH2 and ACYP2 are relevant molecular targets for the neurotoxic effects of oxadiazon, suggesting a potential role of this herbicide in the onset of neurodegenerative diseases.